The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acscentsci.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Catalyzed Selective Formal Insertion of Diazo Compounds into C(sp)–C(sp3) Bonds of Propargyl Alcohols: Access to Alkyne-Substituted All-Carbon Quaternary Centers

Abstract: The construction of all-carbon quaternary centers, especially those containing an alkyne-substituted framework, represents an important challenge in organic synthesis. Here we present a novel Fe-catalyzed selective formal insertion of diazo compounds into C(sp)−C(sp 3 ) bonds of propargyl alcohols under mild conditions that enables the streamlined construction of alkynesubstituted all-carbon quaternary centers. This unique strategy starts with in situ generation of an ester group in the presence of carboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…According to the experimental results as well as previous studies, 20 a plausible reaction pathway was described as shown in Scheme 5. First, with the assistance of fluorescein/blue light/oxygen, NH 4 SCN could smoothly produce the SCN radical.…”
mentioning
confidence: 66%
“…According to the experimental results as well as previous studies, 20 a plausible reaction pathway was described as shown in Scheme 5. First, with the assistance of fluorescein/blue light/oxygen, NH 4 SCN could smoothly produce the SCN radical.…”
mentioning
confidence: 66%
“…The activation of C-H bonds is an effervescent area of work in organic synthesis. [1][2][3][4][5][6][7] The stringent demands that the current concerns on sustainability pose on the chemical industry require the seeking of new methods for the preparation of high-value commodities. [8][9][10] In this scenario, the development of new catalysts that enables the introduction of oxygenated functions into C(sp 3 )-H bonds is a challenge undertaken by many research groups.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal carbenes obtained from diazo compounds have been extensively used in organic synthesis. They can react with various functional groups. Among them, alkynes show a particularly diverse pattern of reactivity .…”
mentioning
confidence: 99%
“…Compared to the well-developed cyclopropenations, the alkynylations involving carbenes for the construction of alkyne-substituted quaternary centers are still underdeveloped (Scheme A, right) . In spite of this, great achievements have been made in the past few decades (Scheme B). , For example, Liang and co-workers described a specific protocol for the synthesis of 1,5-enynes bearing all-carbon quaternary centers via a palladium(0)-catalyzed decarboxylation of allyl 3-arylpropiolates and subsequent insertion of aryldiazoacetates (Scheme B, a) . Recently, a selective Fe-catalyzed formal insertion of diazo compounds into C­(sp)–C­(sp 3 ) bonds of propargyl alcohols in the presence of carboxylic acids was established, which can provide an alternative route to alkyne-substituted all-carbon quaternary centers (Scheme B, b) .…”
mentioning
confidence: 99%
See 1 more Smart Citation